Themes of Stressors, Emotional Fatigue, and Communication Challenges Found in Mobile Care Discussion Sessions With Patients Requiring Lifelong Home Parenteral Nutrition Infusions. Issue 3 (4th June 2020) - Smith, Carol E.; Yadrich, Donna; Wright, Shawna; Ridder, Lavonne; Werkowitch, Marilyn; Bruce, Amanda; Bonar, Jaime Rachelle M.
Abstract: Background: The purpose of this article is to examine themes and topics that emerged from 35 discussion sessions with teens and young adults requiring long‐term home parenteral nutrition (HPN) intravenous infusions. The goal was to gain a more detailed understanding of participants' challenges and successes of living with HPN. Methods: These patients were invited to attend 3 discussion group sessions facilitated by health professionals. A secure iPad Mini was selected as the mobile tablet device for hosting these encrypted audio‐visual group discussions. Content analysis, a standard research data‐sorting technique, was used to summarize the anonymous data. Words, phrases, and topics in patients' discussions were coded and grouped together with similar concepts and subsequently categorized into themes. Results: Themes in these discussions were related to patients' daily, complex management of HPN. These "themes" included having multiple repetitive illness‐related stressors and how those stressors were managed; managing emotions; communication challenges with professionals, family, friends, and using social media; and lastly, the least frequent but no less important theme discussed was how HPN effects their daily lives. Conclusion: Teens and young adults living with lifelong HPN face a variety of unique psychological, physical, and emotional stressors and may benefit from numerous methods for managing these challenges.